Analisis Transaksi Akad Salam dalam Jual Beli Followers, Likes dan Viewers (Studi Kasus Pengguna Instagram Wilayah Makassar) - Sri Ujiana Putri; Shabrina Syifa Salsabila (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
This study aims to identify and analyze salam contract transactions in buying and selling followers, likes and viewers of Instagram social media and the clarity of the object being transacted. This research is a qualitative research (fieldresearch) using a normative approach, phemonology, and case studies. The results showed several things. First, there is a discrepancy with the pillars and conditions of the salam contract, namely the object of the transaction. Buying and selling followers, likes and Instagram viewers do not fulfill the object of the transaction because of the obscurity of the object/item. Second, the object of the contract/goods contains an element of ambiguity due to the seller knowingly knowing and being aware that the object of the transaction is not pure with a mixture of active followers and passive followers which is proven to be of very different quality. Third, the existence of openness and dishonesty between the seller and the buyer, causing a violation of the provisions of the salam contract and the law of buying and selling in Islamic law.